Revistas y redes en la conformación del campo intelectual latinoamericano - Lozoya López, Ivette; Zamorano Díaz, César (Ariadna Ediciones, 2021)
The works collected in this book converge in the recognition of journals, intellectuals and writers as decisive instances of research and expand the possibilities of envisioning the training of readers capable of recognizing the materiality of their proposals, insofar as they are inscribed in broader discussions of social configuration. Intellectuals and magazines that assimilate social functions where the echoes of larger assemblages overflow to propose new features focused from Latin American countries, which warn of the signs of emerging itineraries in dispute.